PENERAPAN 303 KUHP TERHADAP JUDI SECARA ONLINE KAITANNYA DENGAN PROSES PENYELIDIKAN DI POLRESTA SAMARINDA - Hedar Hedar (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT An increase in the mode of the crime of gambling are higher this could be seen from the prolifertion of types of gambling, such  Togel, gambling tail, white coupon gambling, especially with the development of technology that also form the gambling was progressing as exampes of gambling by means of the use of internet technology. Problem gambling is already stipulated in the articles of KUHP namely article 303 and article 303 bis and laws ITE contaned in article 27 paragraph (2).Formulation of the problem as follows the factors that lead to criminal acts in the online gambling community samarinda city and the constraints faced by the authorities in addressing and eradicating the crime of online gambling is happening in society samarinda city. Research used in preparing this thesis, is empirical juridical approach, the specification of the research is descriptive. Data used in this research is secondary data, methods of data collection using interviews and the research literature. Methods of  presenting the data in this research use descriptive method.The results showed :The factors that lead to online gambling in samarinda namely economic factors, factors of unemployment, factors and try fad, educational factors, and environmental factors.Constraints faced by the police samarinda in tackling and infrastructure that exist within the scope of the police, the police further education, proving incomplete and gambling are organized. Suggestions in this study were police officers in the field of information technology in online gambling disclosure and utilization of mass media to investigate and phenomenon of online gambling Key Word  : Gambling, Internet, Online Gambling